Capital Inflows, Sterilization, and Commercial Bank Speculation : The Case of the Czech Republic in the Mid-1990's - Christensen, Jakob (IMF Working Papers; Working Paper ;, 2004)
The paper analyzes the relationship between large-scale capital inflows and sterilization efforts in the Czech Republic during 1993-96 using a vector autoregression (VAR) model, which consists of domestic credit, foreign reserves, and domestic and foreign interest rates. The analysis finds that despite initial success in sterilizing capital inflows, this strategy proved increasingly costly and ultimately unsustainable as domestic interest rates attracted more capital inflows. The commercial banks exploited a profitable sterilization game, whereby they borrowed cheaply abroad and invested the funds domestically in high-yielding sterilization bonds.